The Effect Of Sharia Bond, Sharia Stock and Import Export On Indonesia’S Economic Growth - Cindy Clara Afifah; Isnaini Harahap; Wahyu Syarvina (Penerbit Merdeka Kreasi, 2023)
The economic activities that Islam encourages are business activities such as sale and purchase, investment, and other factors that boost economic growth. In addition to the Sharia capital market, imports and exports also influence economic growth in Indonesia. The study aims to find out the impact of sharia bonds, sharia stock, and import exports on Indonesian economic growth. This research is quantitative research with an associative approach. The data used comes from the Central Statistical Authority (BPS) and the Financial Services Authority (OJK). The analysis used in this study was a double linear regression analysis, used EVIEWS 10. The results of the research show that: 1) Sharia bonds (X1) partially influence the growth of the Indonesian economy. 2) Sharia stock (X2) partially influence Indonesia's economic growth. 3) Exports Imports (X3) Partially Imports Imports influence Indonesia's economic growth. 4) Simultaneously that, all of the dependent variables have an impact on Indonesia economic growth in 2016-2021.